A systematic review of the activity and impact of emergency care practioners in the NHS. Issue 10 (13th July 2013) - Hill, Harry; McMeekin, Peter; Price, Christopher
Abstract : Background: The NHS has seen a great expansion in the number of emergency care practitioners (ECPs) working in prehospital, primary and acute care settings since the role was introduced in 2003. This paper updates and expands on two previous reviews of ECP roles by identifying and discussing all empirical studies to date that examined the impact of ECP services in the NHS. Objectives: To summarise the national evidence-based literature on the impact of ECPs on healthcare delivery, effectiveness of practice and related health service resource use. Methods: Searches in MEDLINE, EMBASE and CINAHL databases, and two internet search engines (Google and Google Scholar). Identified publications were screened for relevance and quality before a description and synthesis of their findings. No statistical comparison was undertaken. Results: Studies from the peer-reviewed literature (n=15) and project reports (n=6) were included. Overall, there was evidence that investment in ECP roles is beneficial for the quality of care reported by patients and cost efficiency savings. There was clear support from staff and patients for ECP services, and a number of studies of high methodological quality described care processes (diagnosis, investigations instigated and treatment initiated) provided by ECPs to be equivalent to or better to that provided by practitioners with traditional roles. Prehospital ECPs provided 'added value' by treating more patients at the scene thereby reducing unnecessary referral to emergency departments. It was often unclear whether the ECP intervention was part of a larger service change and/or new investment. Conclusions: Successful implementation of the ECP role has been described. Further evaluations should consider whether the beneficial impact of the role transfers equally across all operational settings and patient groups, and is not just a reflection of new investment in clinical services.